FACTORS DRIVING THE USE OF MOBILE BANKING AT PT. BANK CENTRAL ASIA (TBK) MANADO - Langelo, Jessica L.H.P.; Pandowo, Merinda (Universitas Sam Ratulangi, 2014)
Information technology is fundamentally changing the banking industry worldwide. Understanding of how demographic characteristics, social factors, and perceptions and influence consumer attitudes toward mobile banking adoption can allow banks to create solutions and plans to attract consumers to use their mobile banking services, thus enabling them to gain a greater share in the market banking. Especially in the banking market as the current BCA Manado where rapid development. is able to create ease and satisfaction to consumers who use these services. The population are 100 respondent of BCA consumers. The method used in this study is a quantitative method by distributing questionnaires to obtain primary data. The results which explains that there are twelve variables that encourage consumers to use the BCA bank (m-BCA services) which then formed five factors and there are eight factors that had no significant effect on the use of mobile banking services BCA Manado region. Five factors are formed service, trust, promotion Enriching mobile, and function of mobile banking, while eight variables significantly the cost is customer, customer behavior, customer satisfaction, reliability, perceived usefulness, real time to access and perceived ease of use. Keyword: mobile banking, trust, promotion, enriching mobile, function